Prevalence of Allergic Rhinitis on Children with Stunting Using ISAAC Questionnaire - Sarumpaet, Venny Tiursani; Dermawan, Arif; Lasminingrum, Lina (Syntax Literate, 2024)
Stunting is a chronic nutritional problem caused by many factors, including the condition of nutritional intake in infants. Malnutrition reduces body immunity so it is considered as a risk factor for inflammation in children. Allergic rhinitis is an inflammatory disease of the nasal mucosa caused by allergic reactions in patients. This study aims to determine the prevalence of allergic rhinitis in stunting patients in Kabupaten Bandung. This research is a descriptive study, data was taken by multistage cluster randomized sampling based on inclusion and exclusion criteria, in Kabupaten Bandung from the October 2019 to December 2019. The data obtained will be presented in the form of tables and diagrams. Result. From a total of 436 children age 2 – 5 years old with stunting, there were 188 children (43.11%) with allergic rhinitis and 245 children (58.6%) who did not suffer from allergic rhinitis. Most ages were in the range of 48-60 months as many as 77 children (40.95%), with the most sex being male as many as 100 children (53.19%), the most reported comorbidities were tonsillitis as many as 74 children (39.36%). Of the total 188 respondents, only 19 children (8.5%) had a history of atopy. In this study, the prevalence of allergic rhinitis in stunting children was 43.11%.